Development of Corn Milk Yoghurt Using Mixed Culture of Lactobacillus delbruekii, Streptococcus salivarus, and Lactobacillus casei - SEDARNAWATI YASNI; AYUNI MAULIDYA (Bogor Agricultural University, Indonesia, 2014)
The main objective of this research was to diversify the utilization of corn as commercial commodity by a corn-based new product development in the form of yoghurt. The first step was carried out to make corn yoghurt with the addition of fresh milk into heated corn extract using mixture starter of Lactobacillus delbruekii, Streptococcus salivarus, and Lactobacillus casei and the best formulation was determined through hedonic evaluation along with weighing method. The selected formulation from this step was corn extract with the addition of 50% fresh milk. The corn extract was produced from corn kernels that were blended and mixed with water in ratio of 3:1, the mixture was further heated and concentrated until the total volume remained 2/3. Afterwards, this selected formulation was added with sugar and full cream milk powder. The hedonic evaluation results showed that the mixture with 10% sugar and 5% full cream milk powder addition possessed the highest score. Lastly, the selected formulation was observed for physical, microbiological, and chemical assay during 4 weeks period. The ultimate observation concluded that the product could be classified as probiotics with total lactic acid bacteria reached 1.5 x 109 CFU/ml with medium fat content (1.8%).